European phenological response to climate change matches the warming pattern - ANNETTE MENZEL; TIM H. SPARKS; NICOLE ESTRELLA; ELISABETH KOCH; ANTO AASA; REIN AHAS; KERSTIN ALM‐KÜBLER; PETER BISSOLLI; OL'GA BRASLAVSKÁ; AGRITA BRIEDE; FRANK M. CHMIELEWSKI; ZALIKA CREPINSEK; et al. (Global Change Biology, 2006)
Global climate change impacts can already be tracked in many physical and biological systems; in particular, terrestrial ecosystems provide a consistent picture of observed changes. One of the preferred indicators is phenology, the science of natural recurring events, as their recorded dates provide a high‐temporal resolution of ongoing changes. Thus, numerous analyses have demonstrated an earlier onset of spring events for mid and higher latitudes and a lengthening of the growing season. However, published single‐site or single‐species studies are particularly open to suspicion of being biased towards predominantly reporting climate change‐induced impacts. No comprehensive study or meta‐analysis has so far examined the possible lack of evidence for changes or shifts at sites where no temperature change is observed. We used an enormous systematic phenological network data set of more than 125 000 observational series of 542 plant and 19 animal species in 21 European countries (1971–2000). Our results showed that 78% of all leafing, flowering and fruiting records advanced (30% significantly) and only 3% were significantly delayed, whereas the signal of leaf colouring/fall is ambiguous. We conclude that previously published results of phenological changes were not biased by reporting or publication predisposition: the average advance of spring/summer was 2.5 days decade −1 in Europe. Our analysis of 254 mean national time series undoubtedly demonstrates that species' phenology is responsive to temperature of the preceding months (mean advance of spring/summer by 2.5 days°C −1 , delay of leaf colouring and fall by 1.0 day°C −1 ). The pattern of observed change in spring efficiently matches measured national warming across 19 European countries (correlation coefficient r =−0.69, P